An experimental investigation of the phase change process effects on the system performance for the evacuated tube solar collectors integrated with PCMs. (1st December 2018) - Essa, Mohamed A.; Mostafa, Nabil H.; Ibrahim, Mostafa M.
Highlights: Evacuated tube solar collectors integrated with phase change materials are investigated. The phase change process and the system performance are affected by the flow rates. Under high flow rate, the system does not achieve a thermal energy storage benefit. A correlation is presented to express discharge time as a function of temperature. Abstract: This paper presents an experimental investigation of the performance of evacuated tube solar collectors integrated with Phase Change Materials systems. The performance of these systems depends on the thermal charging and discharging of the phase change materials. One of the important heat transfer parameters concerning these systems is the phase change process. Such a process depends on the flow rate of the heat transfer fluid and the environmental conditions. In the present study, a comparative study was carried out for two finned U-tube direct flow collectors. For the first collector paraffin wax was used as a phase change material. While for the second collector the control collector was left empty. Different flow rates were applied to study their effects on both the phase change process and the system performance. It was found that low flow rates allow a complete phase change and achieve the energy storage benefit of the phase change material. When the phase change process was complete, the system delivered its best efficiency. Under high flow rates, the system did not achieve the expected thermal energy storage benefits because the phase change material remained in the solid state. However, the solid phase provided a good insulator for the useful heat and enhanced the system's efficiency. At a flow rate that caused a partial phase change, the system's efficiency deteriorated, but the storage benefit of the phase change material was achieved. A novel correlation is proposed to estimate the hot water supply period according to a required discharge temperature. This correlation is valid for the direct flow finned and U-tube evacuated tube solar collectors integrated with paraffin wax as a phase change material.